Plant Bioactive Metabolites and Their Role in the Prevention and Control of Dental Diseases and Infections. - Prikshit Rampal 1*; Mukesh Chander1 (Emerging Trends in Metabolites, 2026)
The oral diseases, including dental caries and periodontitis, affect masses worldwide, and have historically been managed with synthetic antimicrobials that cause deleterious side effects, leading to mounting bacterial resistance. Consequently, contemporary dentistry is rapidly shifting toward phytomedicine using plant bioactive molecules, such as polyphenols, terpenes, anthraquinones (berberin, eugenol, curcumin, catechins, allicin, and azadirachtin. These compounds offer potent antimicrobial, anti-inflammatory, and tissue-regenerative properties that are crucial for preventing and curing dental pathologies. For disease prevention, phytochemicals actively disrupt microbial homeostasis before infections can fully establish. Extracts from plants like Curcuma sp., Zingiber officinale (ginger) and Aloe vera prevent dental caries by directly inhibiting the growth, biofilm formation, and acidogenic metabolism of Streptococcus mutans by neutralizing bacterial quorum sensing, disrupting extracellular matrix synthesis, and physically preventing pathogens from adhering to the dental enamel. Furthermore, non-abrasive Aloe vera tooth gels exhibit remineralization capacity equivalent for that of standard fluoride formulations, to decay progression. In aid of curative dentistry, plant molecules may be integrated with advanced clinical technologies. In operative dentistry, Antimicrobial Photodynamic Therapy utilizing the natural photosensitizer aloe-emodin achieves near-total disinfection of carious-affected dentin, thereby performing conventional chlorhexidine while actively enhancing micromechanical bond strength and resin tag infiltration of restorative adhesives and curing periodontitis. The green tea extracts resolves chronic gingival destruction by aggressively downregulating host pro-inflammatory cascades and promoting tissue regeneration. In endodontics, natural extracts allow antimicrobial irritants to deeply penetrate complex root canal anatomies and eradicate highly resistant biofilms. Translating these therapeutic successes into predictable clinical cures requires overcoming the low aqueous solubility and rapid metabolic degradation of natural compounds to achieve highly sustainable protocols to prevent and cure oral diseases.
Keywords: Dental Cares; Flavanols; Keywords: Bioactive molecules; Periodontitis; Root Canal Therapy; oral health